Biological Resource Center for Toxoplasma. (20th October 2020) - Rocaboy, Camila; Dardé, Marie-Laure; Aubert, Dominique; Mercier, Aurélien; Ortis, Naïma; Passebosc-Faure, Karine; Riahi, Homayoun; Escotte, Sandie; Gatet, Martine; Villena, Isabelle
The Biological Resource Center (BRC) for Toxoplasma gondii is a certified structure (NF S96-900 standard) that manages the storage of Toxoplasma gondii strains (protozoan parasite) and strain derivatives from human or animal toxoplasmosis to make them available to the scientific community.